PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN NASABAH PADA PT. PEGADAIAN KANWIL I MEDAN - Eunike Oxana Federova Manik; Namira Ufrida Rahmi (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study aims to determine the effect of service quality and facilities partially or simultaneously on customer satisfaction. Everyone definitely needs money to be able to survive and meet their needs. So that people feel confused about who they want to borrow from and fortunately with the availability of PT. Pegadaian Kanwil I Medan, it will make it easier for people to get loans, namely by guaranteeing their personal belongings as collateral for the loan. Customer satisfaction is the feeling felt by the customer, if the customer comes more than once to use pawnshop services, it means that the customer is happy and satisfied with the services and facilities available at PT. Pegadaian. The population in this study are all customers of PT. Pegadaian Kanwil 1 Medan, totaling 244,710. Based on the slovin formula, there are 72 slovin samples. This study used multiple linear regression analysis and data analysis tools to test the hypothesis with SPSS V 25. The results of testing the coefficient of determination in this study obtained an Adjusted R Square value of 0.723, which means that the influence of the independent variables on the dependent variable was 72.3%. The results showed that the variables of service quality and facilities had an effect on customer satisfaction either partially or simultaneously.